What makes therapy work? An exploratory study of the understandings of "expert" psychotherapeutic practitioners - Stein, Dhyan Lorraine (Curtin University, 2010)
This thesis explores the informants of effective psychotherapy derived from subjective and intersubjective practitioner/researcher perspectives. Unlike the empirical model of rationalist, objective precepts, these understandings stem from inductive reasoning that incorporates Aristotle’s (1976) notion of phronesis and Schön’s (1983) model of reflective practice. Essentially, this approach examines the tacit knowledge of ‘expert’ psychotherapists based on multiple collaborative, iterative-generative conversations. Accordingly, this process generated grounded theory characterized by a series of interrelated themes. The most significant of these established that client internalized second-order change is a primary feature of effective psychotherapy. It was also ascertained that client enhanced self-concept and subjective and objective change contribute to internalized second-order change.Secondly, client symptomology, psychological mindedness, reflexivity and openness to change were also viewed as major factors in facilitating this outcome. Thirdly, therapist contributions were recognized as important informants of effective psychotherapy. These include a commitment to emotional truth, authenticity, receptivity, therapeutic presence, clinical acumen and adoption of participant/observer and executive/caring stances. Fourthly, a number of interpersonal processes were identified as influential shapers of client second-order change. Specifically, the relational depth of the client/therapist encounter informed by the parties’ mutuality was considered pivotal.Fifthly, therapeutic turning points operating at covert and overt levels of awareness were highlighted. In keeping with informed discourse, these therapeutic events are described as therapeutic moments, vulnerable moments and present moments. Sixthly, a model of therapist empathy thought to enhance these critical encounters emerged. Finally, a six-phased transtheoretical model to facilitate practitioner effectiveness was presented based on the study’s overarching themes.